Assessing the Economic, Social, and Cultural Impacts of the Tourism Industry in Sudurpaschim, Nepal - Chataut, Ram Kumar; Saud, Hari Singh (NPRC Journal of Multidisciplinary Research, 2025)
Tourism has become a crucial catalyst for development in various regions of Nepal, particularly in the rural and underdeveloped provinces. This study examines the influence of the tourism industry on economic, social, and cultural integration in Sudurpaschim Province, Nepal. A causal-comparative research design employing a quantitative approach was used. Data were collected from 228 respondents across two districts: Doti and Kanchanpur. This study examined the economic, social, and cultural impacts of the tourism industry using three distinct simple linear regression models to assess the relationships.The results indicate a statistically significant positive economic impact of tourism (R² = 0.355, β = 0.596, p < 0.001) and a similarly significant positive social impact (R² = 0.376, β = 0.613, p < 0.001). However, the findings revealed no significant cultural impact (R² = 0.000, β = 0.017, p = 0.795), suggesting that tourism may exert a neutral or potentially negative effect on cultural integration in the region. It may be due to a specific cultural perspective in the area.The findings underscore the pivotal role of tourism in fostering economic development in Sudurpaschim while simultaneously highlighting concerns regarding its cultural ramifications. This study provides valuable insights for policymakers, tourism stakeholders, and development planners, aiming to promote sustainable and inclusive tourism growth.